Persepsi ibu tentang makanan obesogenis sebagai faktor risiko obesitas pada anak sekolah dasar - Elisa Sulistyaningrum; Hamam Hadi; Madarina Julia (Jurnal Gizi Klinik Indonesia, 2015)
Background: Prevalence of children with over nutrition is a global problem that continues to increase every year. Obesity in children have  an obese risk in adulthood. The high prevalence of obesity in children due to poor nutrition. Parents, especially mothers have a great role in determining the chilrdren nutritional intake so mothers understanding to the type of food that causes obesity is very important.Objective: To determine the mother's perception of obesogenic food and its relation to the risk of obesity in elementary school children of Yogyakarta and Bantul.Method: This study was a case-control study. Mothers who have an obese child  (≥ 95 th percentile) as a case and mothers of children with nonobese (<95th percentile) as a control. Primary research locations in the city of Yogyakarta and Bantul district. The samples was selected by using the random sampling method. The minimum sample of cases and controls was 63 people 63 people (1: 1). Data analysis were using Chi-Square statistical tests and conditional logistic regression.Results: Subjects of the study consisted of 244 cases and 244 controls. Chi-Square test showed that mother's perception of the obesogenis food can not be used as a predictor for the occurrence of obesity in children (p>0.05). Children of mothers who have a wrong perception about sweet drinks have a obesity risk 1.85 times greater than children of mothers who have a right perception to sweet drinks. So did for the children of mothers who have a wrong perception of fast food have an obesity risk 1.76 times greater than children who had mothers with the correct perception of the traditional fast food. Then the children of mothers who had a wrong perception of full cream milk and other dairy products have a risk of obesity 3.3 times smaller than the mother who has the correct perception to the full cream milk and other dairy products. Mother's perception about obesogenic foods as risk factor of obesity in children is not influenced by the level of education, household expenditure and maternal work status (p>0.05).Conclusion: Perception mother of obesogenic foods can not be used as a predictor for the occurrence of obesity in children (p>0.05). The level of maternal education, maternal work status and household expenses rather than as a factor does not affect the mother's perception of the food obesogenis.